Laminated piezoelectric film, device, and method for manufacturing laminated piezoelectric film
A laminated piezoelectric film with a thermosetting hard coating layer and optional ultraviolet curable layer addresses thermal stability and adhesion issues, ensuring precise electrode placement and transparency, enhancing operational reliability and cost-effectiveness.
Patent Information
- Application Number
- CN202380037864.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-11
- Filing Date
- 2023-05-10
- Publication Date
- 2024-12-13
AI Technical Summary
Existing piezoelectric films face issues with thermal stability, adhesion, and transparency, particularly when a hard coating layer is applied, leading to potential peeling and displacement of electrodes during heating processes.
A laminated piezoelectric film is developed with a thermosetting hard coating layer on at least one surface, using a fluorine-based resin as the main component, with specific heat shrinkage and adhesion criteria, and optionally paired with an ultraviolet curable hard coating layer, to enhance thermal stability and adhesion.
The laminated piezoelectric film achieves excellent thermal stability, adhesion, and transparency, maintaining electrode position and visual clarity, while supporting precise electrode formation without costly preheating processes.
Smart Images

Figure CN119138127A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a stacked piezoelectric film, a device having the stacked piezoelectric film, and a method for manufacturing the stacked piezoelectric film. Background Art
[0002] In recent years, touch sensors have been introduced into electronic devices such as smartphones and tablet computers as human-machine interfaces that enable intuitive operation. Touch sensors are used to detect a two-dimensional position touched by a finger or a pen (for example, see Patent Document 1).
[0003] In addition, a touch sensor that senses pressing force has recently been developed for the purpose of increasing input information and improving operability. As a method for sensing pressing force, there are, for example, a method for detecting pressing force by a change in electrostatic capacitance when the shell is deformed, a method for detecting a change in resistance value of a pressure-sensitive rubber, and a method for detecting a change in charge of a piezoelectric material. As a piezoelectric film of a touch panel that can detect pressing force (Z coordinate), for example, a piezoelectric body containing polyvinylidene fluoride and polyvinylidene fluoride-tetrafluoroethylene copolymer is known.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Laid-Open No. 5-324203 Summary of the invention
[0007] Problems to be solved by the invention
[0008] In order to maintain the visual confirmation of the display located on the back of the touch panel, such a piezoelectric film is required to be transparent. In addition, sometimes a hard coating layer is laminated on the piezoelectric film to impart scratch resistance, but if the adhesion between the piezoelectric film and the hard coating layer is low, they may peel off, so it is also necessary to have adhesion.
[0009] Furthermore, sensors using piezoelectric films require electrodes to be formed at predetermined positions on the film surface with high precision. The formation of electrodes is often accompanied by heating, and for piezoelectric films with high thermal shrinkage, thermal stability is also required, such as not causing displacement of the electrode position or poor appearance due to thermal shrinkage during the heating process.
[0010] The present invention has been made in view of the above-mentioned technical problems, and an object of the present invention is to provide a stacked piezoelectric film having excellent thermal stability, adhesion and transparency, a device having the stacked piezoelectric film, and a method for manufacturing the stacked piezoelectric film.
[0011] Technical Solution
[0012] The present inventors have found that by providing a thermosetting hard coating layer laminated on at least one surface of a piezoelectric film containing a fluorine-based resin as a main component, a predetermined heat shrinkage rate, adhesion and b * The stacked piezoelectric films each satisfying a specific range can solve the above-mentioned technical problems, thereby completing the present invention. Specifically, the present invention relates to the following contents.
[0013] The present invention relates to a laminated piezoelectric film, comprising: a piezoelectric film containing a fluorine-based resin as a main component; and a thermosetting hard coating layer laminated on at least one surface of the piezoelectric film, wherein the absolute value of the heat shrinkage rate of the laminated piezoelectric film when heat-treated at 100° C. for 30 minutes is less than 1.0% in both the longitudinal direction (MD) and the transverse direction (TD), the adhesion between the piezoelectric film and the thermosetting hard coating layer evaluated based on ASTM D3359 is 4B or more, and the L * a * b * b in the color system * It is not less than -0.7 and not more than 0.7.
[0014] Preferably, an ultraviolet curable hard coating layer is provided on a surface of the piezoelectric film on the opposite side of the laminated piezoelectric film from the thermosetting hard coating layer.
[0015] Preferably, the piezoelectric constant d of the stacked piezoelectric film is 33 It is above 10pC / N.
[0016] Preferably, the total light transmittance of the stacked piezoelectric film is greater than 90%.
[0017] Preferably, the thermosetting hard coating layer includes at least one cured product selected from the group consisting of (meth)acrylic resins, epoxy resins, amino resins, and urethane resins.
[0018] Furthermore, the present invention relates to a device including the stacked piezoelectric film.
[0019] Moreover, the present invention relates to a method for manufacturing a stacked piezoelectric film, which comprises: a coating step of coating a thermosetting hard coating agent on at least one surface of a piezoelectric film having an absolute value of a heat shrinkage rate of more than 2.0% in at least one of the longitudinal direction (MD) and the transverse direction (TD) and a water contact angle of less than 75°; and a heat treatment step of heat treating the coated piezoelectric film at a temperature of more than 110° C. and less than 140° C. for more than 15 seconds and less than 80 minutes.
[0020] Preferably, the manufacturing method includes: a coating step, coating a UV-curable hard coating agent on the surface of the piezoelectric film on the opposite side of the thermosetting hard coating layer; a heat treatment step, heat treating the coated piezoelectric film at a temperature above 40°C and below 100°C; and a UV-curing step, irradiating the coated surface of the UV-curable hard coating agent with UV rays.
[0021] As a method for making the water contact angle of the surface of the piezoelectric film 75° or less, corona treatment is preferable.
[0022] Effects of the Invention
[0023] According to the present invention, there can be provided a stacked piezoelectric film having excellent thermal stability, adhesion, and transmittance, a device including the stacked piezoelectric film, and a method for producing the stacked piezoelectric film. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 1 is a cross-sectional view schematically showing a stacked piezoelectric film 1 as one embodiment of the stacked piezoelectric film of the present invention. DETAILED DESCRIPTION
[0025] Hereinafter, an embodiment of the present invention (hereinafter referred to as “the present embodiment”) will be described in detail with reference to the drawings, but the present invention is not limited thereto and various modifications can be made without departing from the gist of the invention.
[0026] In addition, in this specification, "stacked" means that each layer only needs to be stacked in order, and other layers may be stacked between each layer.
[0027] 《Stacked piezoelectric film》
[0028] The stacked piezoelectric film of the embodiment of the present invention comprises: a piezoelectric film containing a fluorine-based resin as a main component; and a thermosetting hard coating layer stacked on at least one surface of the piezoelectric film, the absolute value of the heat shrinkage rate of the stacked piezoelectric film when heat-treated at 100° C. for 30 minutes is less than 1.0% in both the longitudinal direction (MD) and the transverse direction (TD), the adhesion between the piezoelectric film and the thermosetting hard coating layer evaluated based on ASTM D3359 is 4B or more, and L * a * b * b in the color system * It is not less than -0.7 and not more than 0.7.
[0029] <Characteristics of laminated piezoelectric film>
[0030] The absolute value of the heat shrinkage rate of the laminated piezoelectric film when heat-treated at 100°C for 30 minutes is less than 1.0% in both the longitudinal direction (MD) and the transverse direction (TD). The adhesion between the piezoelectric film and the thermosetting hard coating layer evaluated based on ASTM D3359 is 4B or more, and L* a * b * b in the color system * It is not less than -0.7 and not more than 0.7.
[0031] From the viewpoint of easily obtaining excellent thermal stability, the absolute value of the thermal shrinkage of the laminated piezoelectric film is preferably 0.5% or less in both the machine direction (MD) and the transverse direction (TD). The lower limit is not particularly limited.
[0032] In this specification, the above-mentioned heat shrinkage ratio is a value measured by the method described in Examples described later.
[0033] In this specification, the above-mentioned adhesiveness is evaluated by the method described in Examples described later.
[0034] From the perspective of easily obtaining excellent transparency, the piezoelectric film is preferably * It is preferably -0.5 or more and 0.5 or less, and more preferably -0.3 or more and 0.3 or less.
[0035] In this manual, b * The measurement was conducted in accordance with JIS Z 8722.
[0036] From the viewpoint of easily obtaining excellent transparency, the total light transmittance of the laminated piezoelectric film is preferably 85% or more, and more preferably 90% or more. The upper limit of the total light transmittance is not particularly limited.
[0037] In this specification, the total light transmittance is measured in accordance with JIS K 7361-1.
[0038] From the viewpoint of easily obtaining excellent transparency, the haze value of the laminated piezoelectric film is preferably 2.0% or less, more preferably 1.2% or less, and further preferably 0.8% or less. The lower limit of the haze value is not particularly limited.
[0039] In this specification, the haze value is measured in accordance with JIS K 7136.
[0040] The thickness of the laminated piezoelectric film is preferably 10 μm or more and 200 μm or less, more preferably 20 μm or more and 100 μm or less, and further preferably 30 μm or more and 80 μm or less. If the thickness of the laminated piezoelectric film is 10 μm or more, the mechanical strength is likely to be sufficient. In addition, if the thickness of the laminated piezoelectric film is 200 μm or less, the transparency is likely to be sufficient and it is easy to be used for optical purposes.
[0041] Next, each layer of the stacked piezoelectric film will be described with reference to the drawings.
[0042] Figure 11 is a cross-sectional view schematically showing a laminated piezoelectric film 1 as one embodiment of the laminated piezoelectric film. In the laminated piezoelectric film 1 , a thermosetting hard coating layer 21 is laminated on one surface of a piezoelectric film 11 .
[0043] <Piezoelectric film>
[0044] The piezoelectric film 11 is a film (thin film) having piezoelectricity (the property of converting an applied force into a voltage or the property of converting an applied voltage into a force), and contains a fluorine-based resin as a main component. By containing a fluorine-based resin as a main component, good piezoelectricity and transparency can be obtained compared to a piezoelectric film containing polylactic acid or the like as a main component. In this specification, containing a fluorine-based resin as a main component means that the mass of the constituent components containing the fluorine-based resin is 50% by mass or more relative to the mass of the piezoelectric film.
[0045] The material forming the piezoelectric film 11 is a polymer compound, specifically, a polarizable polymer compound that exhibits piezoelectricity by polarizing the molecular dipoles using a polarization treatment generally referred to as a thermal polarization treatment, a stretched chiral polymer compound that exhibits piezoelectricity by stretching the chiral polymer compound, and the like. Examples of polarizable polymer compounds include: fluorine-based resins; vinyl cyanide-based polymers; vinyl acetate-based polymers; odd-numbered nylons such as nylon 9 and nylon 11; polyureas, and the like. Examples of stretched chiral polymer compounds include: helical chiral polymer compounds such as polylactic acid; polyhydroxycarboxylates such as polyhydroxybutyrate; cellulose-based derivatives, and the like. They can be used alone or in combination of two or more. The piezoelectric film 11 is a polymer compound containing a fluorine-based resin as a main component, and the polymer compound is preferably a fluorine-based resin.
[0046] As fluorine-based resins, there can be listed: polyvinylidene fluoride (PVDF), vinylidene fluoride copolymers (for example, vinylidene fluoride / trifluoroethylene copolymers, vinylidene fluoride / trifluoroethylene / trifluorochloroethylene copolymers, hexafluoropropylene / vinylidene fluoride copolymers, perfluorovinyl ether / vinylidene fluoride copolymers, tetrafluoroethylene / vinylidene fluoride copolymers, hexafluoropropylene oxide / vinylidene fluoride copolymers, hexafluoropropylene oxide / tetrafluoroethylene / vinylidene fluoride copolymers, hexafluoropropylene / tetrafluoroethylene / vinylidene fluoride copolymers); tetrafluoroethylene polymers; trifluorochloroethylene polymers, etc. They can be used alone or in combination of two or more. Among them, from the perspectives of the height, weather resistance, heat resistance, etc. of the obtained piezoelectricity, polyvinylidene fluoride and / or vinylidene fluoride copolymers are more preferred.
[0047] The higher the piezoelectricity, the higher the detection sensitivity. Therefore, the piezoelectric constant d of the laminated piezoelectric film 11 is 33It is preferably 10 pC / N or more, more preferably 12 pC / N or more, and further preferably 15 pC / N or more. It should be noted that in this specification, the piezoelectric constant d 33 This is a value measured by the method described in Examples to be described later.
[0048] The thickness of the piezoelectric film 11 is preferably 10 μm or more and 200 μm or less, more preferably 20 μm or more and 100 μm or less, and further preferably 30 μm or more and 80 μm or less. If the thickness of the piezoelectric film 11 is 10 μm or more, the mechanical strength is likely to be sufficient. In addition, if the thickness of the piezoelectric film 11 is 200 μm or less, the transparency is likely to be sufficient and it is easy to use for optical purposes.
[0049] <Thermosetting hard coating>
[0050] The laminated piezoelectric film 1 includes a thermosetting hard coating layer 21 laminated on one surface of the piezoelectric film 11 .
[0051] By providing the thermosetting hard coat layer 21 , damage to the stacked piezoelectric film 1 can be suppressed, and the transparency of the stacked piezoelectric film 1 can be improved.
[0052] The thermosetting hard coating is a layer of thermosetting resin obtained by curing a thermosetting resin composition. Examples of thermosetting resins include organic thermosetting resins such as (meth) acrylic resins, epoxy resins, amino resins, and urethane resins, and inorganic thermosetting resins such as silicone resins. Among them, organic thermosetting resins are preferred, and (meth) acrylic resins, epoxy resins, amino resins, and urethane resins are more preferred, and (meth) acrylic resins are further preferred, from the perspective of being easy to cure at a relatively low temperature and having good adhesion to the piezoelectric film.
[0053] From the viewpoint of improving the strength of the coating film, adjusting the refractive index, improving the transparency of the laminated piezoelectric film, etc., the thermosetting resin composition may also contain microparticles (organic microparticles and / or inorganic microparticles). Examples of organic microparticles include: organosilicon microparticles, cross-linked acrylic microparticles, and cross-linked polystyrene microparticles. Examples of inorganic microparticles include: synthetic silica particles, talc particles, diatomaceous earth particles, calcium carbonate particles, feldspar particles, quartz particles, aluminum oxide microparticles, zirconium oxide microparticles, titanium oxide microparticles, and iron oxide microparticles. These may be used alone or in combination of two or more.
[0054] If the thermosetting hard coating is too thin, the thermosetting hard coating cannot fully cover the fine concavo-convex shape of the surface of the piezoelectric film, and therefore the effect of reducing the haze of the piezoelectric film may not be fully obtained. On the other hand, if the thermosetting hard coating is too thick, the stress from the outside cannot be fully transmitted to the piezoelectric film, so sometimes the piezoelectricity of the stacked piezoelectric film becomes insufficient. Therefore, from the viewpoint of reducing the haze of the piezoelectric film, the thickness of the thermosetting hard coating is preferably 0.05 μm or more, more preferably 0.1 μm or more, and further preferably 0.5 μm or more. In addition, from the viewpoint of obtaining a stacked piezoelectric film that can fully reflect the piezoelectric properties of the piezoelectric film, the thickness of the thermosetting hard coating is preferably 3.0 μm or less, more preferably 2.0 μm or less, and further preferably 1.5 μm or less. By making the thickness of the thermosetting hard coating within the above range, in the stacked piezoelectric film, it is easy to take into account sufficient piezoelectricity and transparency corresponding to the purpose.
[0055] <Ultraviolet curable hard coating>
[0056] In another embodiment of the stacked piezoelectric film of the present invention, in the stacked piezoelectric film, a thermosetting hard coating is stacked on one surface of the piezoelectric film, and an ultraviolet curable hard coating is stacked on the other surface. Thus, the fine concavoconvex shape of the surface of the piezoelectric film is covered by the hard coating on both sides of the piezoelectric film, and the haze can be further reduced. In addition, the hard coating suppresses thermal shrinkage, so the dimensional stability is improved.
[0057] The ultraviolet curable hard coat is a layer of ultraviolet curable resin. As ultraviolet curable resin, various resins such as polyester, (meth) acrylic, urethane, amide, silicone, epoxy, etc. can be listed, including ultraviolet curable monomers, oligomers, polymers, etc. In addition, ultraviolet polymerization initiators are added to the ultraviolet curable resin. From the perspective of sufficient transparency, the richness of material types and the reduction of raw material prices, (meth) acrylic resins are preferred.
[0058] From the viewpoint of scratch resistance or transparency, the thickness of the UV curable hard coat is preferably 0.3 μm or more, more preferably 0.5 μm or more. In addition, from the viewpoint of piezoelectric properties, the thickness of the UV curable hard coat is preferably 5 μm or less, more preferably 3 μm or less, and further preferably 2 μm or less. By making the thickness of the UV curable hard coat within the above range, the scratch resistance can be sufficiently reduced while the haze is reduced, and high piezoelectric properties can be achieved.
[0059] Although preferred embodiments of the present invention have been described above, the present invention is not limited to the above embodiments. The laminated piezoelectric film 1 may be provided with any layer other than the above-mentioned layers at any position within a range that does not significantly impair its function.
[0060] <Applications of laminated piezoelectric films>
[0061] The laminated piezoelectric film of the present invention is preferably used in devices such as piezoelectric panels including capacitive type and resistive film type touch panels, pressure sensors, actuators for tactile sensing devices, piezoelectric vibration power generators, and flat speakers.
[0062] The piezoelectric panel further includes a common display panel unit such as a liquid crystal display (LCD) below the laminated piezoelectric film.
[0063] The above device is preferably used in mobile phones, smart phones, mobile information terminals, tablet PCs, notebook computers, FA (Factory Automation) equipment, OA (Office Automation) equipment, medical equipment, car navigation systems, and the like.
[0064] 《Method for manufacturing laminated piezoelectric film》
[0065] The stacked piezoelectric film of the present invention can be manufactured by the following method, etc., which includes: a coating process (coating process A), coating a thermosetting hard coating agent on at least one surface of a piezoelectric film having an absolute value of a heat shrinkage rate of more than 2.0% in at least one of the longitudinal direction (MD) and the transverse direction (TD) and a water contact angle of less than 75°; and a heat treatment process (heat treatment process A), heat treating the coated piezoelectric film at a temperature of more than 110°C and less than 140°C for more than 15 seconds and less than 80 minutes.
[0066] As described above, a hard coating is laminated on the piezoelectric film to improve scratch resistance. In addition, a preheating treatment is performed on the piezoelectric film before the heating treatment to avoid poor appearance caused by heat shrinkage, but this will cause cost increase, which is particularly problematic for piezoelectric films with expensive material and processing costs.
[0067] In order to solve this problem, the inventors conducted research on forming a hard coating on a piezoelectric film without preheating the piezoelectric film, and found that by applying a thermosetting hard coating agent to the surface of a piezoelectric film having a water contact angle of less than 75° and heat treating the film at a specified temperature and time, the hard coating can be formed without preheating, thereby providing a stacked piezoelectric film with excellent thermal stability, tightness and transparency at a low cost.
[0068] (Coating process A)
[0069] The water contact angle of the surface of the piezoelectric film to be coated with the thermosetting hard coating agent is 75° or less. By forming the thermosetting hard coating layer on the surface of such a piezoelectric film, the adhesion between the thermosetting hard coating layer and the piezoelectric film can be improved.
[0070] In this specification, the water contact angle refers to the value obtained by dropping a pure water droplet (2.0 μL) on a surface using a contact angle meter FACE CA-V (manufactured by Kyowa Interface Science Co., Ltd.), measuring the contact angle 10 times for 3 seconds after the drop, and calculating the arithmetic average thereof.
[0071] Methods for making the water contact angle 75° or less include methods of subjecting the surface of the piezoelectric film to be coated with the thermosetting hard coating agent to surface modification treatments such as corona treatment, plasma treatment, flame treatment, and ultraviolet irradiation treatment, etc. Among them, corona treatment is preferred because good adhesion can be easily obtained.
[0072] Examples of the thermosetting hard coating agent include the above-mentioned thermosetting resin composition.
[0073] The method for applying the thermosetting hard coating agent is not particularly limited and can be carried out by a known method. Examples of the coating method include: an extrusion nozzle method, a scraper method, a doctor blade method, a rod coating method, a kiss-coating method, a kiss reverse method, a gravure roll coating method, a dip coating method, a reverse roll coating method, a direct roll coating method, a curtain method, and an extrusion method.
[0074] (Heat treatment process A)
[0075] After the coating step A, a heat treatment step A is performed to heat the coated piezoelectric film at 110° C. to 140° C. for 15 seconds to 80 minutes. This allows the formation of the thermosetting hard coat layer without preheating the piezoelectric film.
[0076] The heat treatment temperature of the coated piezoelectric film is preferably above 110°C and below 140°C, more preferably above 120°C and below 130°C. In addition, the heat treatment time is preferably above 15 seconds and below 80 minutes, more preferably above 1 minute and below 40 minutes. If the heat treatment temperature and the heat treatment time are above the lower limit, good thermal stability is easily obtained. In addition, if the heat treatment time and the heat treatment time are below the upper limit, it is not easy to cause the piezoelectric film to deteriorate. Therefore, the haze value, total light transmittance, b * Optical properties and piezoelectricity are not easily deteriorated.
[0077] (Ultraviolet curable hard coat layer forming step)
[0078] A step for forming an ultraviolet curable hard coating layer may be optionally performed after the heat treatment step A. In the ultraviolet curable hard coating layer forming step, an ultraviolet curable hard coating agent is applied to the surface of the piezoelectric film having a thermosetting hard coating layer formed on one side thereof, where the thermosetting hard coating layer is not formed (applying step B). The applied piezoelectric film is heat treated (heat treatment step B), and then irradiated with ultraviolet rays (ultraviolet curing step).
[0079] In the coating step B, the surface of the piezoelectric film to be coated with the ultraviolet curable hard coating agent may be subjected to the same treatment as the surface coated with the thermosetting hard coating agent. Examples of ultraviolet curable hard coating agents include the above-mentioned acrylic resins. In addition, the coating method may be the same as that described for the thermosetting hard coating agent, and may be the same method as the method for coating the thermosetting hard coating agent or a different method.
[0080] Next, in the heat treatment step B, the piezoelectric film coated with the ultraviolet curable hard coating agent is heat treated. From the viewpoint of not easily causing deterioration of the piezoelectric film, the temperature at this time is preferably lower than the temperature of the above-mentioned heat treatment step A. Specifically, the temperature at this time is preferably 40° C. or more and 100° C. or less. In addition, the heat treatment time is preferably 1 minute or more and 60 minutes or less.
[0081] Then, in the ultraviolet curing step, the coated surface is irradiated with ultraviolet rays to form an ultraviolet curable hard coating. The amount of ultraviolet rays irradiated also depends on the coating thickness of the ultraviolet curable hard coating agent, and is preferably 100 mJ / cm in terms of cumulative light intensity. 2 Above and 800mJ / cm 2 The intensity of the ultraviolet rays is not particularly limited, but is preferably 200 mW / cm from the viewpoint of the scratch resistance of the hard coat layer. 2 Above and 500mW / cm 2 the following.
[0082] Example
[0083] The present invention will be further described below with reference to Examples and Comparative Examples, but the present invention is not limited to these Examples.
[0084] The properties of the laminated piezoelectric film of the present invention were measured by the following method. The results are shown in Table 1.
[0085] (Thickness of thermosetting hard coating)
[0086] The laminated piezoelectric films of the embodiment and the comparative example were respectively embedded in epoxy resin, and the epoxy resin block was cut in such a way that the cross section of the laminated piezoelectric film was exposed. The cross section of the exposed laminated piezoelectric film was observed using a scanning electron microscope ("SU3800", manufactured by Hitachi HighTech Co., Ltd.) at an acceleration voltage of 3.0 kV and a magnification of 50,000 times to measure the thickness of the thermosetting hard coating layer in the laminated piezoelectric film.
[0087] It should be noted that the thickness of two locations was measured, and the arithmetic mean thereof was set as the thickness of each thermosetting hard coating layer. In addition, under the above-mentioned observation conditions, the interface of each thermosetting hard coating layer was observed as a substantially smooth line, and in the measurement of the thickness, the distance between the lines was measured.
[0088] (Heat shrinkage)
[0089] The stacked piezoelectric film was cut into a size of 120 mm × 120 mm by the test method according to JIS K 7133, and the line spacing (L0 and T0) before the test of the two lines marked in the longitudinal and transverse directions of the cut test piece was measured. It should be noted that the flow direction of the hard coating agent on the film when applied was set as the longitudinal direction, and the direction perpendicular to the flow direction was set as the transverse direction.
[0090] Next, after heating in a hot air drying furnace heated to a specified temperature (100°C) for a specified time (30 minutes), the state is conditioned at room temperature for at least 30 minutes, and the longitudinal and lateral marking spacing (L and T) are measured again. The changes in the longitudinal and lateral marking spacing (ΔL and ΔT) of the above-mentioned test piece are calculated by the following formulas (1) and (2).
[0091] ΔL=[(L-L0) / L0]×100(%) (1)
[0092] ΔT=[(T-T0) / T0]×100(%) (2)
[0093] Then, the change in the longitudinal spacing (ΔL) of the marking lines is defined as the longitudinal heat shrinkage of the film, and the change in the transverse spacing (ΔT) of the marking lines is defined as the transverse heat shrinkage of the film. "MD" in the table represents the longitudinal heat shrinkage, and "TD" represents the transverse heat shrinkage.
[0094] (Adhesion)
[0095] The adhesion of each stacked piezoelectric film was evaluated using the cross-cutting method. Eleven lines with a spacing of 1 mm were cut vertically and horizontally in the thermosetting hard coating of each stacked piezoelectric film using a cutter to produce 100 grids, which were then attached with a tape (Cellotape (registered trademark) manufactured by NICHIBAN Co., Ltd., with an adhesive force of 4.01 N / 10 mm) and peeled off. Based on ASTM D3359, the proportion of the thermosetting hard coating peeled off from the stacked piezoelectric film was evaluated according to the following evaluation criteria.
[0096] 0B: 65% or more peeling.
[0097] 1B: 35% or more and less than 65% peeling.
[0098] 2B: 15% or more and less than 35% peeling.
[0099] 3B: 5% or more and less than 15% peeling.
[0100] 4B: Less than 5% peeling.
[0101] 5B: No peeling.
[0102] (Haze value)
[0103] The haze value of each of the laminated piezoelectric films of Examples and Comparative Examples was measured using a haze meter ("NDH7000SPII", manufactured by Nippon Denshoku Industries, Ltd.) in accordance with the method described in JIS K 7136.
[0104] (Total light transmittance)
[0105] The total light transmittance of each of the laminated piezoelectric films of Examples and Comparative Examples was measured using a haze meter ("NDH7000SPII", manufactured by Nippon Denshoku Industries, Ltd.) in accordance with the method described in JIS K 7361-1.
[0106] (b * value)
[0107] The L values of the laminated piezoelectric films of the examples and comparative examples were measured using a spectrophotometer ("SD7000", manufactured by Nippon Denshoku Industries, Ltd.) according to the method in accordance with JIS K 8722. * a * b * b in the color system * value.
[0108] (piezoelectric constant d 33 value)
[0109] Piezoelectric constant d of each of the laminated piezoelectric films of the example and the comparative example 33Using a piezoelectric constant measuring device ("PiezoMeter System PM300", manufactured by PIEZOTEST), the sample was clamped at 0.2N and the generated charge was read when a force of 0.15N and 110Hz was applied. 33 The actual measured value of is a positive value or a negative value depending on the front or back of the film to be measured, but the absolute value is described in this specification.
[0110] [Example 1]
[0111] A resin film (thickness 120 μm) formed of polyvinylidene fluoride (manufactured by KUREHA Co., Ltd.) having a logarithmic viscosity of 1.1 dl / g was uniaxially stretched at a stretching ratio of 4.2 times. After stretching, a DC voltage was applied between a ground electrode and a needle-shaped electrode while increasing from 0 kV to 12.0 kV, thereby performing polarization treatment to obtain a piezoelectric film. The heat shrinkage of the piezoelectric film when heat-treated at 100°C for 30 minutes was -5.3% in the longitudinal direction (MD) and 1.5% in the transverse direction (TD). In addition, the piezoelectric constant d of the piezoelectric film is 33 It is 16.0pC / N, and the water contact angle on the surface is 80°.
[0112] One surface of the piezoelectric film was subjected to corona treatment until the water contact angle reached 70°.
[0113] The surface of the piezoelectric film subjected to the corona treatment was coated with a thermosetting hard coating agent containing 10 parts by mass of acrylate DA105 (manufactured by Arakawa Chemical Industries, Ltd.) and 4 parts by mass of isocyanate CL102H (manufactured by Arakawa Chemical Industries, Ltd.) as a curing agent and diluted with methyl ethyl ketone (MEK), and heat-treated at 130°C for 40 seconds while fixing the film ends in the TD direction, thereby obtaining a laminated piezoelectric film having a thermosetting hard coating layer thickness as described in Table 1. [Examples 2, 3, and 4]
[0114] A laminated piezoelectric film was obtained in the same manner as in Example 1 except that the heat treatment time was changed to the time described in Table 1.
[0115] [Example 5]
[0116] The surface of the piezoelectric film on the opposite side of the thermosetting hard coating layer of the laminated piezoelectric film obtained in Example 1 was coated with an ultraviolet curable hard coating agent BS CH271 (produced by Arakawa Chemical Industries, Ltd.) and heat treated at 80°C for 2 minutes at a rate of 400 mJ / cm 2 The accumulated light amount was irradiated with ultraviolet rays, thereby obtaining a laminated piezoelectric film having an ultraviolet curable hard coating layer with a thickness of 1.0 μm.
[0117] [Example 6]
[0118] A laminated piezoelectric film was obtained in the same manner as in Example 5 except that the heat treatment temperature was changed to the temperature described in Table 1.
[0119] [Example 7]
[0120] A laminated piezoelectric film was obtained in the same manner as in Example 5 except that the heat treatment temperature and the heat treatment time were changed to the temperature and time described in Table 1.
[0121] [Comparative Example 1 and Comparative Example 2]
[0122] A laminated piezoelectric film was obtained in the same manner as in Example 1 except that the heat treatment time was changed to the time described in Table 1. It should be noted that the laminated piezoelectric film of Comparative Example 2 could not be subjected to thermal shrinkage and piezoelectric constant d due to poor film appearance such as wrinkles. 33 's evaluation.
[0123] [Comparative Examples 3 and 4]
[0124] A laminated piezoelectric film was obtained in the same manner as in Example 1 except that the heat treatment temperature and heat treatment time were changed to the temperature and time described in Table 1. It should be noted that the laminated piezoelectric film of Comparative Example 3 could not be subjected to thermal shrinkage and piezoelectric constant d due to poor film appearance such as wrinkles. 33 's evaluation.
[0125] [Comparative Example 5]
[0126] A laminated piezoelectric film was obtained in the same manner as in Example 1 except that the piezoelectric film was not subjected to corona treatment.
[0127] [Comparative Example 6]
[0128] The acrylic thermosetting hard coating agent was replaced with an ultraviolet curable resin composition containing amorphous silica, and after heat treatment, a UV irradiation device CSOT-40 (manufactured by GS YUASA Co., Ltd.) was used at 400 mJ / cm 2 The laminated piezoelectric film was obtained in the same manner as in Example 2 except that the accumulated light amount was irradiated with UV. The hard coating layer of the obtained laminated piezoelectric film was not cured, so the heat shrinkage and optical properties (haze value, total light transmittance, b * value).
[0129] [Table 1]
[0130]
[0131]
[0132] As shown in Table 1, in Examples, the heat shrinkage was low, the adhesion was good, and the brightness was high. Therefore, it was confirmed that the present invention can obtain a laminated piezoelectric film excellent in thermal stability, adhesion, and transparency.
[0133] Description of Reference Numerals
[0134] 1: laminated piezoelectric film; 11: piezoelectric film; 21: thermosetting hard coating layer.
Claims
1. A laminated piezoelectric film, comprising: a piezoelectric film containing a fluorine-based resin as a main component; and a thermosetting hard coating layer laminated on at least one surface of the piezoelectric film, The absolute value of the heat shrinkage rate of the laminated piezoelectric film when heat-treated at 100° C. for 30 minutes is less than 1.0% in both the longitudinal direction MD and the transverse direction TD. The adhesion between the piezoelectric film and the thermosetting hard coating layer evaluated based on ASTM D3359 is 4B or more, L * a * b * b in the color system * It is not less than -0.7 and not more than 0.
7.
2. The laminated piezoelectric film according to claim 1, in, An ultraviolet curable hard coating layer is provided on a surface of the piezoelectric film opposite to the thermosetting hard coating layer.
3. The laminated piezoelectric film according to claim 1 or 2, in, The piezoelectric constant d of the stacked piezoelectric film 33 It is above 10pC / N.
4. The laminated piezoelectric film according to claim 1 or 2, in, The total light transmittance of the stacked piezoelectric film is greater than 90%.
5. The laminated piezoelectric film according to claim 1 or 2, in, The thermosetting hard coating layer includes at least one selected from the group consisting of a (meth)acrylic resin, an epoxy resin, an amino resin, and a urethane resin. 6 . A device comprising the stacked piezoelectric film according to claim 1 .
7. A method for manufacturing a stacked piezoelectric film, the method for manufacturing a stacked piezoelectric film include: A coating step of coating a thermosetting hard coating agent on at least one surface of the piezoelectric film having an absolute value of a heat shrinkage ratio of 2.0% or more in at least one of a longitudinal direction MD and a transverse direction TD and having a water contact angle of 75° or less; and The heat treatment step is to heat treat the applied piezoelectric film at a temperature of 110° C. to 140° C. for 15 seconds to 80 minutes.
8. The method for manufacturing a laminated piezoelectric film according to claim 7, in, The method for manufacturing the stacked piezoelectric film comprises: A coating step of coating a UV-curable hard coating agent on the surface of the piezoelectric film opposite to the thermosetting hard coating layer; a heat treatment step of heat-treating the coated piezoelectric film at a temperature of 40° C. to 100° C.; and In the ultraviolet curing step, the surface coated with the ultraviolet curable hard coating agent is irradiated with ultraviolet rays.
9. The method for manufacturing a laminated piezoelectric film according to claim 7 or 8, in, The method for making the water contact angle 75° or less is corona treatment.
Citation Information
Patent Citations
Electrostatic capacity type touch panel
JP1993324203A
Cited By
Piezoelectric film, touch panel, and piezoelectric film manufacturing method
US12757638B2
Transparent piezoelectric laminated film and touch panel
US12779498B2
